Excitation of forced modes in the dielectric disk resonator-diffraction grating system - A.I. Fisun; O.N. Sukhoruchko; O.I. Belous (Журнал нано- та електронної фізики)
In this work the strip-like diffraction grating influence on the spectrum of “whispering gallery” modes of the disk dielectric resonator was studied experimentally. The conditions of single-mode excitation in a wide frequency range had been defined.